Parasite-Specific IL-17-Type Cytokine Responses and Soluble IL-17 Receptor Levels in Alveolar Echinococcosis Patients. (30th August 2012) - Lechner, Christian J.; Grüner, Beate; Huang, Xiangsheng; Hoffmann, Wolfgang H.; Kern, Peter; Soboslay, Peter T.
Abstract : Alveolar Echinococcosis (AE) caused by the cestode Echinococcus multilocularis, is a severe helminth infection of man, where unrestricted parasite growth will ultimately result in organ failure and fatality. The tissue-infiltrative growth of the larval metacestode and the limited efficacy of available drugs complicate successful intervention in AE; patients often need life-long medication, and if possible, surgical resection of affected tissues and organs. Resistance to AE has been reported, but the determinants which confer protection are not known. ln this study, we analyzed in patients at distinct stages of Alveolar Echirococcosis, that is cured, stable and progressive AE, as well as in infection-free controls, the cellular production and plasma levels of pro-inflammatory cytokines lL-17A, lL-17B, lL-17F and their soluble receptors lL-17RA (slL-17RA) and IL-17RB (sIL-17RB). Significantly elevated levels of IL-17B and slL-17RB were observed, whilst lL-17F and slL-17RA were reduced in patients with AE. Similarly, the cellular production of lL-17F and slL-L7RA in response to E. multilocularis antigens was low in AE patients, while levels of slL-17RB were highly enhanced. These observations suggest immune-modulating properties of E. multitocularis on lL-17 cytokine-mediated pro-inflammatory immune responses; this may facilitate the tissue infiltrative growth of the parasite and its persistence in the human host.